2021
DOI: 10.1186/s43066-021-00161-0
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal plants with hepatoprotective potentials against carbon tetrachloride-induced toxicity: a review

Abstract: Background Carbon tetrachloride (CCl4) is a well-characterized hepatotoxic agent. With rising cases of liver diseases, the identification, assessment, and development of hepatoprotective agents from plants source has become imperative. Main body With arrays of literature on plants with hepatoprotective potentials, this review sourced published literatures between 1998 and 2020 and systematically highlighted about 92 medicinal plants that have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 91 publications
1
22
0
Order By: Relevance
“…It is worth mentioning that the EE is rich in TPC, and there is a direct relation between antioxidant activity and TPC that was previously reported for extracts of other plants . The promising results of the antioxidant activity and richness of the extract with polyphenolic compounds encouraged us to utilize this extract as a hepatoprotective drug as it is well known that the main mechanism of the action of polyphenols as hepatoprotective drugs is mediated by decreasing the oxidation stress level in the liver. , …”
Section: Results and Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…It is worth mentioning that the EE is rich in TPC, and there is a direct relation between antioxidant activity and TPC that was previously reported for extracts of other plants . The promising results of the antioxidant activity and richness of the extract with polyphenolic compounds encouraged us to utilize this extract as a hepatoprotective drug as it is well known that the main mechanism of the action of polyphenols as hepatoprotective drugs is mediated by decreasing the oxidation stress level in the liver. , …”
Section: Results and Discussionmentioning
confidence: 83%
“…42 The promising results of the antioxidant activity and richness of the extract with polyphenolic compounds encouraged us to utilize this extract as a hepatoprotective drug as it is well known that the main mechanism of the action of polyphenols as hepatoprotective drugs is mediated by decreasing the oxidation stress level in the liver. 43,44 3.4. Virtual Human Metabolism Prediction.…”
Section: Resultsmentioning
confidence: 99%
“…71 Alternatively, CCl 4 is commonly applied in hepatotoxicity research as a model as hepatopreventive and hepatoprotective agents, including natural compounds. 24,72 In a review by Ugwu and Suru, 72 the orally administrated dose of CCl 4 to animals was between 0.2 mL (e.g., mice) and 4 mL (e.g., Wistar rats). This review showed that the oral dose of the control, which is generally the plant extract silymarin, is around 50 mg similar to that of the EOP extract used in the present study.…”
Section: Food and Function Papermentioning
confidence: 99%
“…This review showed that the oral dose of the control, which is generally the plant extract silymarin, is around 50 mg similar to that of the EOP extract used in the present study. In most of the cases, the beneficial effects (e.g., downregulating liver marker enzymes, restoring the liver tissue architecture, or improving antioxidant defense) of the plant extracts were explored through the oral administration of more than 100 mg. 72 Therefore, the hepatopreventive and anti-fibrotic potential of the EOP extracts also seems promising.…”
Section: Food and Function Papermentioning
confidence: 99%
“…The liver is the prime organ in the human body that helps in maintaining metabolic and physiologic homeostasis. It plays a central and important role in many metabolic pathways especially those related to growth and development, fighting off diseases, production and supply of nutrients and energy, metabolism of proteins, carbohydrates and fats, bile secretion and storage of vitamins (Ouassou et al, 2021;Sami et al, 2019, Tafere et al, 2019Ugwu & Suru 2021;Wahid et al, 2016). Furthermore, the liver is also a crucially important organ in drug metabolism and protecting humans against the harmful impact of many toxic agents.…”
Section: Introductionmentioning
confidence: 99%